AKIBAT HUKUM PERJANJIAN KERJASAMA KOPERASI DENGAN BANK DI DENPASAR DALAM PEMBERIAN KREDIT PEMILIKAN RUMAH (KPR) - Wijana Putri, Diah; Dharmawan, Ni Ketut Supasti; Dewi Kasih, Desak Putu (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
The law consequence of joint agreement beetwen Koperasi and Bank at Denpasar in order to give KPR. Problem shown up in related matter on placement of Koperasi on the joint agreement on KPR from Bank? And what is the law consequence related to the jammed KPR in given KPR from Bank? Writing method using empiris yuridis method which is descriptive. Based on the research the result of the placement of Koperasi in joint agreement to facilitate KPR are as a facilitator and guarantor the member of Koperasi. If the credit jammed in order to return the KPR from the member of koperasi then as the joint agreement regulation as a result Koperasi have to buyback the house which is funded by the KPR itself. Then the conclusion in joint agreement between Koperasi and Bank in order to give the KPR plecement between Koperasi and Bank is not balance because as a facilitator and guarantor Koperasi should not having responsibility to buy back the house which has been sold and on the credit agreement of money loaning is only happen between the Bank and the member of Koperasi as the regulation article 1340 point (1) KUHPerdata, the agreement is just valid between both sides that make the agreement.
Keywords: High Population, House Needs, KPR, Joint Agreement